SYNTAX: CRITERIA OF GRAMMATICAL NOMENCLATURE AND ANALYSIS - Gispert-sauch, Ana (2013)
This article attempts to systematize basic syntactical ideas in order to have access to texts of classical Latin. The authoress adopts the criterion of functionality according to which she analyzes the four basic morphological grammatical categories. Noun, adjective, verb and adverb presenting the function that is proper to each one, but noting at the same time that these functions of syntax can be expressed by other morphological categories. It also presents, as a basic question, the terminology of different grammatical trends.